Application Of SMMM Method for Maintenance Digital Signature in Government - Luh Ayu Diah Fernita Sari (International Journal of Engineering and Emerging Technology, 2021)
Digital signature is an application that really helps administrative activities in the government sector. Various benefits are felt now that the digital signature has been validated as a valid signature. This makes users use digital signatures more and more. Therefore, audiences need to do good documentation and training so that they can produce a digital signature application that is easy to understand, use and more efficient. In addition, with the many different needs in each service, there are also many integrated systems that are connected to the digital signature application. this needs to be done an audit for system maintenance so that the system can avoid bugs. Based on these problems, a digital signature system audit is needed to support a better application. In this study, a system audit will be carried out using the Software Maintenance Maturity Model method. Research with this method emphasizes the maintenance support system audit. This method is able to audit the digital signature system in system maintenance and support and produce conclusions if the most important thing to do is change, namely the Maintenance Process / Service Definition key process which has a capability level value of 1.67